Students' Perception of the Use "Game to Learn English" in Improving Vocabulary Mastery: A Case Study at Twelve Grade Students of SMAN 1 Baros - Kamila, Nada Shofa; Arisya, Putri; Handayani, Ika; Setiadi, Yudi (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to find out how students' perception of the use of game in increasing vocabulary mastery. This research was conducted in SMAN 1 Baros Kab. Serang. A qualitative method was used for this research and there were 30 students in the twelve class as the sample of this research. In collecting the data, this research used a questionnaire, interview, and observation. The findings took the result that most students agree and gave a positive response than the negative one of the uses of game in increasing vocabulary mastery. Game as a media gave the advantages and contribution to both the students to improve vocabulary mastery. 1) This media made the students feel enjoyable in learning English and made the learning process became fun; 2) This media gave a significant impact and increased students' vocabulary mastery and improved their English; 3) Using this media, the students had a chance to improve their English whenever they want to learn it. The conclusion could be taken that the students had positive responses and perceptions in using game as a media for increasing vocabulary mastery.